Kształtowanie społeczeństwa chrześcijańskiego. Wybrane aspekty działalności łacińskich ojców Kościoła V i VI w. - Wygralak, Paweł (Annales Missiologici Posnanienses, 2016)
The article outlines the main directions of the evangelization of the Church Fathers in the 5th and 6th centuries and the numerous obstacles which they encountered in their pastoral ministry. The spreading of pagan practices, magic and all kinds of superstitions were still visible even among the baptized people. Another problem they had to face, no less difficult to overcome, was a moral dissolution, as well as rampant alcoholism. Hence their sermons so often featured merciful God, ready to forgive every person. They also pointed some ways to deepen one’s faith. Thus they tried to form a Christian society, guided by the spirit of the Gospel in every sphere of life.